Effects of drying techniques and storage on raw material safety and stability of phytochemicals of hempedu bumi (Andrographis paniculata (Burm.f.) Wall. ex Nees) - Salleh, Nor Shariah (2017)
Controlling the quality of finished herbal products with regard to safety aspect begins with proper production, harvesting and postharvest handling systems. However, there is very limited information that gives an overview on the safety and quality of hempedu bumi or Andrographis paniculata focusing on drying techniques and storage duration. Therefore, the objective of this study was to ascertain the effects of drying and storage on safety and stability of phytochemicals of A. paniculata.